Anti-CTLA-4 generates greater memory response than anti-PD-1 via TCF-1 - Stephen Mok; Huey Liu; Didem Ağaç Çobanoğlu; Nana-Ama A. S. Anang; James J. Mancuso; E. John Wherry; James P. Allison (Proceedings of the National Academy of Sciences, 2025)
The effects of T cell differentiation arising from immune checkpoint inhibition targeting cytotoxic T lymphocyte–associated antigen 4 (CTLA-4) and programmed cell death protein 1 (PD-1) on the immunological memory response remain unclear. Our investigation into the effects of anti-CTLA-4 and anti-PD-1 on memory T cell formation in mice reveals that memory T cells generated by anti-CTLA-4 exhibit greater expansion, cytokine production, and antitumor activity than those from anti-PD-1. Notably, anti-CTLA-4 preserves more T cell factor-1 (TCF-1)+ T cells during priming, while anti-PD-1 leads to more thymocyte selection-associated high mobility group box (TOX)+ T cells. Experiments using conditional Tcf7 - or Tox -knockout mice highlight that TCF-1 is essential for the memory response generated by anti-CTLA-4, whereas TOX deletion alone in T cells has no effect on the response to anti-PD-1. Deepening our understanding of how checkpoint inhibition affects memory response is crucial for advancing our understanding of the enduring impacts of these immunotherapies on the immune system.